Phosphocholine cytidylyltransferase MoPct1 is crucial for vegetative growth, conidiation, and appressorium-mediated plant infection by Magnaporthe oryzae - Xu, Zhe; Tong, Qi; Lv, Wuyun; Xiao, Yu; Wang, Zhengyi (Frontiers in Microbiology, 2023)
Phosphatidylcholine (PC) plays crucial biological roles in eukaryotic cells. In Saccharomyces cerevisiae, apart from phosphatidylethanolamine (PE) methylation pathway, PC is also synthesized via CDP–choline pathway. Phosphocholine cytidylyltransferase Pct1 is the rate-limiting enzyme to catalyze the conversion from phosphocholine to CDP–choline in this pathway. Here, we report the identification and functional characterization of an ortholog of the budding yeast PCT1 in M. oryzae, named MoPCT1. Targeted gene deletion mutants of MoPCT1 were impaired in vegetative growth, conidiation, appressorium turgor accumulation and cell wall integrity. Also, the mutants were severely compromised in appressorium-mediated penetration, infectious growth and pathogenicity. Western blot analysis revealed that cell autophagy was activated by the deletion of MoPCT1 under nutrient-rich conditions. Moreover, we found several key genes in PE methylation pathway, such as MoCHO2, MoOPI3 and MoPSD2, were significantly up-regulated in the ΔMopct1 mutants, indicating that a pronounced compensation effect exists between the two PC biosynthesis pathways in M. oryzae. Interestingly, in the ΔMopct1 mutants, histone H3 was hypermethylated and expression levels of several methionine cycling-related genes were significantly up-regulated, suggesting that MoPCT1 is involved in histone H3 methylation and methionine metabolism. Taken together, we conclude that the phosphocholine cytidylyltransferase coding gene MoPCT1 plays important roles in vegetative growth, conidiation and appressorium-mediated plant infection by M. oryzae.